2016
DOI: 10.3390/nu8040239
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Patterns and the Risk of Hypertension among Chinese: A Cross-Sectional Study

Abstract: Epidemiological studies of different dietary patterns and the risk of hypertension among a middle-aged Chinese population remain extremely scare. Thus, the aim of this study was to identify dietary patterns and investigate the relationship between dietary patterns and the risk of hypertension among Chinese adults aged 45–60 years. The present cross-sectional study includes 2560 participants who reported their dietary intake using a validated food frequency questionnaire (FFQ). Dietary patterns were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 39 publications
1
43
1
2
Order By: Relevance
“…First, processed and cooked meats contain a lot of salt and nitrite. As mentioned before, high salt intake can increase the risk of diabetes [38]. In addition, nitrate as one of the common added preservatives in processed meats can convert to nitrosamine compounds, which have been reported to increase the risk of diabetes [39].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…First, processed and cooked meats contain a lot of salt and nitrite. As mentioned before, high salt intake can increase the risk of diabetes [38]. In addition, nitrate as one of the common added preservatives in processed meats can convert to nitrosamine compounds, which have been reported to increase the risk of diabetes [39].…”
Section: Discussionmentioning
confidence: 88%
“…Simultaneously, pickled vegetables that were loaded on this pattern contain high amounts of salt. Our previous study has shown that high intake of salt can increase the risk of hypertension [38], an important risk factor for diabetes. In short, the above possibilities can't be ruled out in our study.…”
Section: Discussionmentioning
confidence: 98%
“…It is noteworthy that soy products are related to the prevention of atherosclerosis due to their antioxidant action on circulating lipids in plasma, as well as due to the presence of soluble fibers that act especially on the decrease of total cholesterol and LDL-C, since they reduce triglyceride levels besides exerting an anti-platelet aggregation effect [39,40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure was measured twice at the house of the participants after a rest of 5 minutes by the trained interviewer using standard mercury sphygmomanometer and appropriate-sized cuff according to a standard protocol, and the blood pressure was recorded in average. The hypertension was defined as an average SBP at least 140 mmHg, and/or DBP at least 90 mmHg without any anti-hypertensive medication use [ 19 ].…”
Section: Methodsmentioning
confidence: 99%